Letter - Young, James
035-0049-001 The Association of Engineering and Shipbuilding Draughtsmen General Secretary: JAMES YOUNG. Registered Office: 96 ST. GEORGE'S SQUARE, LONDON, S.W.1. Telegraphic Address: "DRAFTINEER, SOWEST, LONDON." Telephone—Victoria 0747 and 0748. Registered under T.U. Acts No. 1691T. Please address all Communications for Head Office to "THE GENERAL SECRETARY." Your Ref: International VT/AEC/JRD/88. THIS REFERENCE MUST BE QUOTED IN REPLYING TO THIS LETTER Ref: JY/HA/T.U.C. 16th October, 1950. Sir Vincent Tewson, General Secretary, Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. Dear Sir Vincent, SPAIN I have to acknowledge receipt of your letter of the 13th inst., and thank you for the information contained therein regarding the above. Yours sincerely, James Young, General Secretary. 292/946/35/49(i)